Attitude towards rural library services among youths in Malaysia - Mohamad Yusoff, Mohamad Zaim Fahmi; Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (TextRoad Publication, 2013)
This study aims to discover the attitude towards rural library services among youths in Malaysia. In addition, it considers the individual factors that might influence attitudes towards the services offered. This is a correlational study in nature, and uses a developed questionnaire to obtain the data needed. A total of 400 respondents among rural youths from 16 selected rural libraries in four states of Peninsular Malaysia were chosen. Based on the analysis performed, it can be concluded that rural youths have a favorable attitude towards the services offered by local libraries. Moreover, further analyses show that the frequency of attending rural libraries has a positive relationship with attitude towards rural library services. A number of recommendations have been highlighted, and it is hoped that these will help concerned parties in constructing an effective strategy for developing rural libraries in Malaysia.